Pengaruh Media Audiovisual Terhadap Hasil Belajar Sekolah Dasar Dalam Pembelajaran Tematik Terpadu - Imam Taufiq; Muhammadi Muhammadi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
The research is caused by low learning outcomes of students . Research aims to determine the effect of use of visual audio media on integrated thematic learning in the fourth grade of elementary school. This type of research is quantitative in the form of quasy experiment design. The design uses by The Nonequivalent Pretest-postest Control Group Design. Using the convenience sampling, where the population consists of several elementary schools in District of group 4  of West Padang. The study was conducted at grade 4thA and 4thB in SDN 23 Marapalam. The selected sample is grade 4thA  as the experimental class and grade 4thB as the control class. The instrument used in this study was an objective test with multiple choice types. The data analysis technique applies inferential statistical test with test-t. Proven score thitung = 2.42 and ttabel with a level of 0.05 and dk = n1 + n2 - 2 = 30 + 30 - 2 = 58 obtaine ttabel = 2,002. The data of  thitung> ttabel with 2.42> 2,002 can be concluded that the visual audio media has a positive effect on the learning outcomes on integrated thematic learning in 4th grade class of Elementary School.Keywords: Visualaudio media, learning outcomes, integrated thematic learning